Design of a Portable Integrated Fluid–Structure Interaction-Based Piezoelectric Flag Energy-Harvesting System - Haochen Wang; Xingrong Huang; Zhe Li; Le Fang (Fluids)
Fluid–structure interaction-based energy-harvesting technology has gained significant attention due to its potential for energy conversion. However, most existing studies primarily focus on energy capture, resulting in incomplete systems with limited portability and a lack of integrated circuitry. To address these limitations, this study presents a portable, integrated piezoelectric flag energy-harvesting system that achieves a complete closed-loop conversion from fluid kinetic energy, through structural strain energy, to electrical energy. The system utilizes an upstream bluff body to generate vortex-induced vibrations, a downstream support structure that maintains operational stability, and an internally integrated wiring channel that enables overall energy conversion. Charge–discharge experiments on the energy storage unit enable a comprehensive evaluation of system performance, marking the first efficiency measurement of a fully integrated energy-harvesting system. Experimental results demonstrate the first quantified map of losses across all conversion stages in a portable piezo-flag platform, highlighting the system’s potential for powering small-scale, low-power self-sustaining devices. This work establishes a reference framework and provides a novel technological pathway for advancing practical applications of fluid-induced energy harvesting, contributing to the development of autonomous power sources in various engineering fields.